Topical application of cinnamon (cinnamomum burmanii) essential oil has the same effectiveness as minoxidil in increasing hair length and diameter size of hair follicles in male white Wistar rats (rattus norvegicus) - Laura Indriana; Wimpie Pangkahila; I Gusti Made Aman (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2018)
Introduction: In aging process, the hair experiences thinning and the hair shaft becomes more fragile due to decreased regeneration of hair. Cinnamon essential oil contains cinnamaldehyde compounds which have a vasodilating effect on blood vessels and stimulating IGF-1 can increase fertility and prevent hair loss. Methods: This study was an experimental study with a post test only control group design carried out in the laboratory animal unit of the pharmacology section of the Udayana University medical faculty. In this study 30 male white rats (Rattus norvegicus) wistar lines were sheared 4cmx4cm which were divided into three groups: negative (aquades) control group (2% minoxidil), treatment group with cinnamon essential oil (concentration 100 %) for 30 days. Results: The average hair length of aquades (P0) was 5.88 ± 0.36 mm, minoxidil group 2% (P1) 7.4 ± 0.20 mm. , cinnamon essential oil group (P2) 8.32 ± 0.18 mm In the diameter size of hair follicles in the three groups showed the mean diameter size of hair follicles was significantly different (P <0.05). The average results of the group hair follicle diameter (P0) were 79.73 ± 30.68 µm, group (P1) 127.07 ± 38.20 µm and group (P2) 130.91 ± 49.96 µm. The LSD test results on hair length measurements between the three groups showed a very significant difference (P <0.01). Group P0 and P1-1,51 mm, group P0 and P2-2,44 mm group P1 and P2 0,92 mm. The results of LSD hair follicle diameter P0 and P1 -47.34 µm (P <0.05), P0 and P2 -51.18 µm (P <0.01), P1 and P2 -3.84 µm (P> 0 , 05) Conclusion: The application of topical cinnamon essential oil increases hair length and diameter size of male wistar rat hair follicles as effectively as topical minoxidil 2%.